Using Gasoline-like Fuel Obtained from Waste Automobile Tires in a Spark-ignited Engine - Öztop, Hakan Fehmi; Varol, Y.; Altun, S.; Firat, M. (Taylor & Francis Inc, 2014)
An experimental study on performance and exhaust emission of a spark-ignited engine fueled by gasoline-like fuel obtained from waste automobile tires using the prolysis process was performed in this study. Gasoline-like fuel has a higher octane number than unleaded gasoline; however, it has higher in viscosity in comparison to unleaded gasoline, which limited the use of gasoline-like fuel in neat form. Therefore, gasoline-like fuel was blended with unleaded gasoline from 0% to 100% with an increment of 10%, volumetrically. Obtained blends were then used in a spark-ignited engine. It was observed that the test engine was normally run up to blended fuel containing gasoline-like fuel of 60%. It is concluded that gasoline-like fuel can be partially substituted for the gasoline fuel up to 60% in blended form in terms of performance parameters and emissions without any engine modification.
Keywords: waste automobile tires; pyrolysis; waste treatment; gasoline-like fuel; alternative fuel